Analysis And Simulation Of Computer Networks On Campus Tuban Institute Technology And Business Uses Cisco Package Tracking - Amran, Ali; Aji Pangestu, Moch. Rizqi (Innovative: Journal Of Social Science Research, 2024)
In an educational institution that has computer-based courses, it is mandatory to have a computer laboratory. As is the case with research carried out at the Tuban Institute of Technology and Business which has several study programs so it is mandatory to have a computer laboratory for continuity of learning. which was used as a reference for the author's research in planning how to implement the ITB Tuban online security optimization online system. The author will use the Access Control List (ACL) method for network access control. Organizing data access traffic by system administrators, so that administrators can determine everything that can be accessed or not accessed by users. Simulation and implementation of computer networks at the Tuban Institute of Technology and Business using Cisco Packet Tracker still needs further development. From the Cisco Packet Tracker network configuration that the author created, it is concluded that the Cisco Packet Tracing network can function well and successfully. The function of the Cisco Packet Tracer that researchers understand here is that it can be used to assemble a network or topology that is applied in the real world, such as at the Tuban Institute of Technology and Business. Apart from that, the author can analyze a well-connected network, by looking at latency, if the network has low latency then the results are positive.